"Gender" and "race" in feminist pedagogy - in the context of a book chapter - Vida, Gergő (Autonomy and Responsibility Journal of Educational Sciences, 2022)
The study processed: Mechthild Nagel: Teaching Feminist Pedagogy on Race and Gender: Beyond the Additive Approach?